Emergence, interpretations and translations of IWRM [Integrated Water Resources Management] in South Africa - Movik, S.; Mehta, L.; van Koppen, Barbara (2016)
South Africa is often regarded to be at the forefront of water reform, based on Integrated Water Resources Management (IWRM) ideas. This paper explores how the idea of IWRM emerged in South Africa, its key debates and interpretations and how it has been translated. It maps out the history, main events, key people, and implementation efforts through a combination of reviews of available documents and in-depth semi-structured interviews with key actors. While South Africa sought to draw on experiences from abroad when drawing up its new legislation towards the end of the 1990s, the seeds of IWRM were already present since the 1970s. What emerges is a picture of multiple efforts to get IWRM to 'work' in the South African context, but these efforts failed to take sufficient account of the South African history of deep structural inequalities, the legacy of the hydraulic mission, and the slowness of water reallocation to redress past injustices. The emphasis on institutional structures being aligned with hydrological boundaries has formed a major part of how IWRM has been interpreted and conceptualised, and it has turned out to become a protracted power struggle reflecting the tensions between centralised and decentralised management.